Children's Social and Emotional Development in Islamic Perspective - Gumiandari, Septi; Selamet, Selamet; Nafi'a, Ilman (Journal of Islam and Science, 2021)
Anti-social behaviors in children is now common. Aggressive behavior, bullying, egocentrism, fighting, prejudice and so on indicate the failure of parenting and teacher education to social and emotional development in children. This study aims to analyze the development of children's social emotions from an Islamic perspective. Through the literature study approach, there are 3 stages of social emotional development in Islam: (1) the first stage starts from birth to 7 years of age. At this stage, ethics education must be taught to children through continuous stimulus, response and imitation because the child's cognitive development is not yet perfect; (2) the second stage starts from 7 to 15 years of age. This stage is called the tamyiz stage in Islam. Children can tell the difference between good and bad. At this stage parental supervision should be increased; and (3) the third stage from 15 years of age and over. Children must already have knowledge, understanding and habits of commendable behavior, because this praiseworthy behavior is always repeated and accustomed to in the first and second stages. In this case, the family plays an important role in shaping the personality of children who are mature in dealing with problems that arise along with social and emotional development. In Islam, the problems faced by children will definitely be in accordance with their respective capacities and can still be overcome. Through problems, their faith and devotion were tested by Allah SWT. Patience and fortitude are one's potential. With intelligence given by God, children can easily know and understand the nature of every challenge and difficulty. Therefore, children must always be educated so they always have positive prejudice (husnudzan) rather than negative prejudice (suudzan), both for themselves, others and Allah.